Clinical outcomes of pre-loaded ultra-thin DSAEK and pre-loaded DMEK. Issue 1 (16th October 2020) - Romano, Vito; Pagano, Luca; Gadhvi, Kunal A; Coco, Giulia; Titley, Mitchell; Fenech, Matthew Thomas; Ferrari, Stefano; Levis, Hannah J; Parekh, Mohit; Kaye, Stephen
Abstract : Objective: To compare clinical outcomes and complications between pre-loaded ultra-thin Descemet stripping automated endothelialkeratoplasty (pl-UT-DSAEK) and pre-loaded Descemet membrane endothelial keratoplasty (pl-DMEK). Methods and analysis: Comparative study in patients with endothelial dysfunction associated with Fuchs endothelial corneal dystrophy and pseudophakic bullous keratopathy who underwent pl-UT-DSAEK or pl-DMEK transplants. For both groups, the tissues were pre-loaded at the Fondazione Banca degli Occhi del Veneto (Venice, Italy) and shipped to The Royal Liverpool University Hospital (Liverpool, UK). Best corrected visual acuity (BCVA) and re-bubbling rates were the main outcome measures. Results: 56 eyes of 56 patients were included. 31 received pl-UT-DSAEK and 25 received pl-DMEK. At 12 months, BCVA (LogMAR) was significantly better for pl-DMEK (0.17±0.20 LogMAR) compared with pl-UT-DSAEK (0.37±0.37 LogMAR, p<0.01). The percentage of people that achieved ≥20/30 was significantly higher in the pl-DMEK group. The rate of re-bubbling, however, was significantly higher for pl-DMEK (44.0%) than for Pl-UT-DSAEK (12.9%), p<0.01. Conclusion: Pl-DMEK offers better BCVA than pl-UT-DSAEK. The higher re-bubbling rate associated with pre-loaded DMEK is of concern.